Twenty-two years of HIV infection in Bhutan: epidemiological profile - Tshering, Pandup (J Virus Erad, 2016)
AIMS: To describe the HIV epidemiology in Bhutan. METHODS: Data from the database of people living with HIV infection in Bhutan, survey reports from the National STI and HIV/AIDS Control Programme from the Ministry of Health and published literature on HIV in Bhutan were reviewed. RESULTS: Bhutan continues to have a low HIV prevalence with only 470 cases reported by the end of 2015. However, there is a slow but steady recent increase in the number of cases. The main mode of transmission is unsafe heterosexual practice in the general population and is occurring mostly in urban and business districts. More than half of cases have been diagnosed in only three districts. Although the number of cases among key populations such as sex workers and intravenous drug users remains significantly low, the information available remains very limited. There is only scarce published literature on HIV in Bhutan and an absence of a strategic surveillance system. A high level of sexually transmitted infections and multiple sexual relationships represent the existing threats that may fuel a larger epidemic. CONCLUSIONS: Bhutan has a maintained a low HIV prevalence over the past two decades, which is reflected in the national response to HIV. However, with the presence of existing and newly emerging risk factors, this response needs to adapt continually. To ensure that HIV prevalence remains low, it is crucial to invest in a strategic information system to monitor rates of infections to guide the public health response.